Blind spots of dynamic capabilities: A systems theoretic perspective - Robert Burisch; Veit Wohlgemuth (Journal of Innovation & Knowledge (JIK), 2016)
Dynamic capabilities remain one of the most popular, but also one of the most controversial topics in current knowledge and innovation research. This study exposes strengths and weaknesses of existing conceptualizations of dynamic capabilities by using a systems theoretic lens. Systems theory suggests that organizations operate in environments they cannot fully understand. Thus, organizational action patterns inevitably involve simplification, selectivity and uncertainty leading to inherent blind spots in every kind of strategic action. As the resulting insight, fully flexible organizational capabilities might not be achievable and continuous adaptation to every kind of environmental change cannot be possible from a systems theoretic perspective. Accordingly, this work discusses empirical difficulties that derive from the preceding argumentation and outlines a corresponding re-conceptualization of the dynamic capabilities concept.
Keywords: A14; D81; O31; O35; M10; 650; Dynamic capability; Systems theory; Complexity